Survey on initial management of acute pancreatitis in Latin America - Lluís, Núria (2023)
Objective: The population of Latin America harbors the highest incidence of gallstones and acute biliary pancreatitis, yet little is known about the initial management of acute pancreatitis in this large geographic region. Participants and methods: We performed a post hoc analysis of responses from physicians based in Latin America to the international multidisciplinary survey on the initial management of acute pancreatitis. The questionnaire asked about management of patients during the first 72 h after admission, related to fluid therapy, prescription of prophylactic antibiotics, feeding and nutrition, and timing of cholecystectomy. Adherence to clinical guidelines in this region was compared with the rest of the world. Results: The survey was completed by 358 participants from 19 Latin American countries (median age, 39 years [33–47]; women, 27.1%). The proportion of participants in Latin America vs. the rest of the world who chose non-compliant options with clinical guidelines were: prescription of fluid therapy rate other than moderate (42.2% vs 34.3%, P = .02); prescription of prophylactic antibiotics for severe (10.6% vs 18.0%, P = .002), necrotizing (28.5% vs 36.9%, P = .008), or systemic inflammatory response syndrome-associated (21.2% vs 30.6%, P = .002) acute pancreatitis; not starting an oral diet to patients with oral tolerance (77.9% vs 71.1%, P = .02); and delayed cholecystectomy (16.2% vs 33.8%, P < .001). Conclusions: Surveyed physicians in Latin America are less likely to prescribe antibiotics and to delay cholecystectomy when managing patients in the initial phase of acute pancreatitis compared to physicians in the rest of the world. Feeding and nutrition appear to require the greatest improvement.